MENINGKATKAN KEMAMPUAN MENGENAL ANGKA 1-10 PADA ANAK USIA 3-4 TAHUN MELALUI KEGIATAN BERMAIN VARIATIF DENGAN MEDIA LOOSE PART DI SPS BOUGENVILLE 20 RAMBIPUJI JEMBER - Khodijah, Khodijah; Sugiarto, Muhammad Agus; Wirawan, Oliva Lili Wangsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to enhance number recognition skills through varied play methods using loose parts media for children aged 3-4 years at SPS Bougenville 20 Rambipuji Jember. The expected benefit for children is an increased ability to recognize numbers through varied play methods using loose parts media. The method used is classroom action research, aimed at improving number recognition from 1-10 for children aged 3-4 years through varied play activities with loose parts media. The subjects of this research are 20 children aged 3-4 years. During the observation process, the researcher was directly involved in the research both inside and outside the classroom. The results of the research in Cycle I and Cycle II showed that: in Cycle I, 5 children or 25% received the Not Developed (BB) score, while 12 children or 60% received the Developing (MB) score. In Cycle I, there was an increase where 3 children or 15% out of 20 children scored Developing as Expected (BSH) and the Developing Very Well (BSB) score did not experience an increase, remaining at 0%. In Cycle II, the ability to recognize numbers 1-10 in children aged 3-4 years through varied play activities with loose parts media at SPS Bougenville 20 Rambipuji Jember reached the success indicator of 80%. With 4 children or 20% out of 20 children achieving the Developing as Expected (BSH) score, while the Developing Very Well (BSB) score was 16 children or 80% out of 20 children. In this Cycle II, the number of children who received the Developing (MB) and Not Developed (BB) scores was 0%.